Recurrent Unilateral Vulvar Syringoma Mimicking Treatment-Resistant Condyloma Acuminata: A Case Report and Review of the Literature - Saeed Baradwan; Mohammad Alyafi; Haneen Al-Maghrabi; Sumaih Shinawi (Healthcare, 2026)
Background: Vulvar syringoma is a rare benign adnexal neoplasm originating from eccrine sweat ducts. Although syringomas most commonly occur in the periorbital region, vulvar involvement is uncommon and frequently underrecognized. Due to its nonspecific clinical appearance, vulvar syringoma may mimic more common vulvar conditions, resulting in delayed diagnosis and repeated ineffective treatments. Case Presentation: A 41-year-old multiparous woman presented with a several-year history of recurrent pruritic papular lesions involving the right vulva. The lesions were repeatedly diagnosed as condyloma acuminata and treated with topical imiquimod, cryotherapy, carbon dioxide laser ablation, and local excision, without sustained improvement. Persistent symptoms and recurrence prompted repeat surgical excision. Histopathological examination revealed a well-circumscribed dermal lesion composed of multiple small eccrine ducts, cysts, and epithelial cords embedded within a dense sclerotic fibrotic stroma. The ducts were lined by two layers of bland cuboidal epithelial cells and demonstrated characteristic comma-shaped and tadpole-like configurations, confirming the diagnosis of vulvar syringoma. No cytologic atypia, increased mitotic activity, dysplasia, or malignancy was identified. The postoperative course was uncomplicated, with satisfactory wound healing and symptomatic improvement during follow-up. Conclusions: Vulvar syringoma should be considered in the differential diagnosis of persistent or treatment-resistant vulvar papules, particularly when lesions recur despite conventional therapy for presumed condyloma acuminata or other benign vulvar disorders. Early biopsy and histopathological evaluation remain essential for establishing an accurate diagnosis, preventing unnecessary interventions, and guiding appropriate management.